The ‘Senatusconsultum Claudianum’ and the Mysterious ‘Lex’ Concerning the Status of Children Born to Free Women Cohabiting with Slaves (G. 1,86 - Kacprzak, Agnieszka (Zeszyty Prawnicze, 2020)
The starting point of this article is the relation between the provision of the SC Claudianum which turned the children born to a free woman by a slave into slaves, and the analogous regulation of the mysterious lex which Gaius mentions in § 86 of Book One of his Institutiones. The fact that almost the same provision appears in two diﬀerent enactments has attracted the attention of many scholars. Some have concluded that the lex in question must have applied to Latins or peregrines, but not to Roman citizens. Others on the other hand ruled out the possibility of the Senatusconsultum containing a provision on children, since their status depended directly on the lex. I claim that both of the regulations which Gaius describes are authentic and both applied to Roman citizens. Notwithstanding obvious analogies, they were not identical. Not only did they address diﬀerent social problems, but they also laid down diﬀerent procedures for the acknowledgement of the slave status of the children. Once we have clarified the relation between these regulations, we are in a better position to understand both the way in which the SC Claudianum functioned as a whole, and its presumable aim. I devote the last part of my article to the latter problem. I argue against with the claim that the aim of the Senatusconsultum was to punish the women and hence to stop them from cohabiting with slaves. On the contrary, such liaisons were a familiar phenomenon in Roman society, as the epigraphical material shows, and they were accepted, providing they observed well-defined conditions and were under the control of the slave’s master. Te main aim of the SC Claudianum was to delineate the bounds within which the cohabitation of free women with slaveswas admissible.